An EST-SSR Marker, bu099658, and its Potential Use in Breeding for Yellow Rust Resistance in Wheat - (:unkn) unknown (CZECH ACADEMY AGRICULTURAL SCIENCES, 2014)
EST-SSR markers, derived from the A and B genomes of wheat were used to identify molecular markers associated with yellow rust resistance. For this purpose, bulk segregant analysis was performed using 114 EST-SSR primer pairs. They were screened on the parent genotypes and resistant/susceptible DNA pools from the cross between Izgi2001 (resistant male parent) x ES14 (susceptible female parent) at the seedling and adult plant stage. An EST-SSR marker, bu099658, generated the 206 bp DNA fragment that was present in the resistant parent and resistant bulk, but it was not present in the susceptible parent and the susceptible bulk. To investigate its association with Yr genes, 20 individuals of NILs were also amplified with BU099658 and the 206 bp marker fragment was obtained only in Yr1/6 x Avocet S. Additionally, bu099658 was screened on 65 genotypes which possessed different Yr genes/gene combination(s) and Yr1. The results indicate a close linkage of bu099658 with the Yr1 gene.
Keywords: Bulk Segregant Analysis (BSA); Marker-Assisted Selection (MAS); Puccinia striiformis f.sp tritici; Triticum aestivum L.; Yr1; TRITICUM-AESTIVUM L.; LENGTH-POLYMORPHISMS; GENETIC-LINKAGE; DNA; IDENTIFICATION; SELECTION; LOCATION; REGION